The last time we spoke : a story of loss - Mechanic, Jesse (Street Noise Books, 2025)
"When he was a teenager, Jesse Mechanic's mother passed away after a long struggle with cancer. In this memoir, he looks back on that time, and on the ways that experience followed him throughout his life. Struggling with school while dealing with attentional problems and the overwhelming tsunami of grief, this book tells the story of Mechanic's slow work to figure out a life for himself. It's about obsessive-compulsive disorder, intrusive thoughts, and depression--straight-A's turning to straight F's, and smiles to blank stares. It's about what loss can teach us, and how trauma can be both debilitating and beautiful. It's about standing in dark rooms for long enough for your eyes to adjust."--